2019
DOI: 10.1103/physreve.100.030201
|View full text |Cite
|
Sign up to set email alerts
|

Complex dynamics of interacting fronts in a simpleA+BCreaction-diffusion system

Abstract: Pattern interaction has so far been restricted to systems with relatively complex reaction schemes, such as activator-inhibitor systems, that lead to rich spatio-temporal dynamics. Surprisingly, a simple second-order chemical reaction is capable of generating similar complex phenomena, such as attractive or repulsive interaction modes between the localized reaction zones (or fronts). We illustrate the latter statement both analytically and numerically with two initially separated A + B → C reaction-diffusion f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This model considers two dimensions (length and width) without the height of the main channel and neglects the wall interaction effects. A 2D approach was successfully applied in multiple works on microfluidic diffusion and reaction systems [ 42 , 44 , 46 , 54 , 55 , 56 ]. The laminar flows of the reacting solutions in such systems are strictly parallel to the “x” axis in the main channel due to a very low Reynolds number.…”
Section: Resultsmentioning
confidence: 99%
“…This model considers two dimensions (length and width) without the height of the main channel and neglects the wall interaction effects. A 2D approach was successfully applied in multiple works on microfluidic diffusion and reaction systems [ 42 , 44 , 46 , 54 , 55 , 56 ]. The laminar flows of the reacting solutions in such systems are strictly parallel to the “x” axis in the main channel due to a very low Reynolds number.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 It was shown that these simple structures can evolve to unexpected behaviors, for example, when one reactant is sandwiched between two pools of the other one, two A + B -C fronts can interact together in the form of attractive or repulsive collective dynamics, depending on the initial distance between the fronts. 29 It was recently shown that simple A + B -C reactions can also exhibit spatiotemporal oscillations, provided that the reaction combines with hydrodynamics. [30][31][32][33] In reactive fluids, natural convection can indeed arise spontaneously from changes in the composition/temperature of the system, further inducing in situ local gradients in the physical properties (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that these simple structures can evolve to unexpected behaviors, for example, when one reactant is sandwiched between two pools of the other one, two A + B → C fronts can interact together in the form of attractive or repulsive collective dynamics, depending on the initial distance between the fronts. 29…”
Section: Introductionmentioning
confidence: 99%